BLOKCHAIN: Financial Recording System Innovation in the Digital Age - Pakpahan, Mika Yohana (PT FORMOSA CENDEKIA GLOBAL, 2022)
The rise of corruption cases and cases of financial record errors is currently causing a lot of losses for the state. For this reason, a solution is needed in the form of the latest financial recording system which has several features that are easy to operate and use in the field of activities and various types of financial transactions. Blockchain is a technology developed to support the era of information disruption. It offers an alternative solution that can represent ever-growing data or datasets. This paper is intended to provide an overview of Blokchain and examples of its application in the field of record keeping. This paper uses a comprehensive method that focuses on identifying, collecting, and interpreting all available research that aims to answer the existing problems in a complete, detailed and comprehensive manner.